Rules for the global environment - Horst Siebert (Kiel Institute for the World Economy (IfW), 2008)
The paper looks at the global environment as a public good and as a sink for CO2-emissions. It discusses problems to be solved in institutional arrangements to protect global environmental media and looks at criteria for allocating the costs of emission reduction and emission rights. It analyzes institutional mechanisms that stabilize CO2-agreements and reviews the Kyoto Protocol, the perspectives for its successor and EU emission trading. The paper also reviews arrangements for biodiversity and existing multilateral arrangements.
Keywords: Q54; D62; F02; H41; Q02; D62; 330; Global warming; Emission reduction; Emission rights; Institutional Mechanisms; Kyoto Protocol; Post-Bali negotiations; Public good; Internationale Umweltpolitik; Klimaschutz; Biodiversität; Umweltabkommen; Welt; Emissionshandel; EU-Staaten